Histological features suggestive of survival in patients with renal cell carcinoma and tumor thrombus: A single-center experience - Wang, Tao; Huang, Yan; Yang, Luojia; Yang, Yang; Li, Di; Zhang, Xiangyi; Ding, Xiaohui; Wang, Baojun; Ma, Xin (Frontiers in Oncology, 2022)
Purpose: To evaluate the impact of histological subtype on the survival of patients with renal cell carcinoma (RCC) and tumor thrombus (TT). Patients and methods: We retrospectively analyzed 350 patients with RCC and TT admitted to Chinese People’s Liberation Army General Hospital between January 2006 and June 2021. The patients underwent radical nephrectomy and thrombectomy using robot-assisted laparoscopic, laparoscopic, or open surgery. The clinical and pathological parameters of the patients were taken from their medical records. Survival was calculated with the Kaplan–Meier method. Univariate and multivariate Cox regression analyses were performed to evaluate the prognostic significance of variables on overall survival (OS) and progression-free survival (PFS). Results: The median follow-up duration was 36.0 (17.9-75.3) months. TT levels 0–IV were observed in 132 (37.71%), 43 (12.29%), 134 (38.29%), 20 (5.71) and 21 (6.00%) patients, respectively. Papillary (pRCC), clear cell, and other histological subtypes of RCC were detected in 28 (8.00%), 286 (81.71%), and 36 (10.29%) patients, respectively. Compared to the clear cell cohort, collecting systemic invasion (46.43 vs. 25.17%; p = 0.030) and lymph node metastasis (39.29 vs. 11.54%; p < 0.01) were more common in the pRCC cohort. Kaplan–Meier analyses showed that patients with pRCC and other subtypes had significantly worse OS and PFS compared to patients with the clear cell subtype (p < 0.05). Multivariate analyses revealed that histology was independently associated with reduced OS and PFS, including among patients without lymph node and distant metastasis (N0M0). Conclusion: Papillary or other subtypes have a considerably shorter OS and PFS compared to clear cell subtype in RCC patients with TT. Strict follow-up and surveillance should be performed for papillary or other subtypes RCC with TT.